Structural and photodetection studies of hydrothermally grown anatase TiO2 nanomaterial. (2023) - Sharma, Sonam; Verma, Arpit; Chaudhary, Priyanka; Singh, Ajeet; Ravi Kant Tripathi, Monu Gupta; Yadav, B.C.
Graphical abstract: Highlights: TiO2 nanostructure synthesised via a simple and low cost hydrothermal method. The detailed structural analysis was done by rietveld refinement analysis. Structural analysis was done and anatase phase confirmed by XRD analysis. The photodetection properties were studied. Exhibiting high external quantum efficiency and high responsivity. Abstract: TiO2 nanomaterial was successfully synthesized via a cost-effective hydrothermal method with a precursor involving titanium tetra isopropoxide (TTIP). The surface morphological and elemental characteristics were confirmed by scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) respectively. Optical properties of the grown nanomaterial were evaluated using UV–Visible spectroscopy and a 3.45 eV bandgap was estimated from the Tauc plot. From X-ray diffraction (XRD) studies, it was confirmed that prepared nanomaterial possesses crystalline structure with anatase phase. Photodetection of the fabricated photodetector device was carried out under the ambient atmospheric conditions result in responsivity of 15.58 mA/W under 80 μW/cm 2 power of incident radiation. The response time and recovery time of the fabricated device find out to be 12.62 sec and 11.89 sec respectively.